Evaluation of Juice Production Characteristics and Analysis of Characteristic Flavor Components of Phyllanthus emblica Fruit Varieties - Zifen ZHENG; Xiaowei CHEN; Bo ZOU; Yuanshan YU; Gengsheng XIAO; Lukai MA (Shipin gongye ke-ji)
In order to explore the processing suitability of different Phyllanthus emblica varieties and provide reference for the development of Phyllanthus emblica juice processing industry, this paper took 8 Phyllanthus emblica varieties mainly grown in Guangdong and Guangxi Provinces as raw materials to determine the physical and chemical indexes, active components, antioxidant capacity and volatile aroma components of the fruit juice. Correlation analysis, principal component analysis, cluster analysis and "reasonably-satisfaction" multidimensional value theory were used to establish the evaluation method of the suitability of Phyllanthus emblica juice production. The results showed that the juice quality of different varieties had significant differences (P<0.05), among which the contents of total phenol, total flavone, ascorbic acid, fumaric acid, ellagic acid and naringin were significantly different, while the juice yield, pH and soluble solid content were little different. A total of 68 volatile aroma components were detected, and 15 aroma components with ROAV>1 were selected. Trans-2-decenoaldehyde, n-octyl aldehyde and nonylaldehyde were the main aroma components. Six principal components were extracted through principal component analysis, and the cumulative variance contribution rate reached 96.033%. Combined with cluster analysis, the quality index was simplified into seven representative indexes: sugar-acid ratio, juice yield, total sugar, browning degree, gallic acid, malic acid and lactic acid. The evaluation model of Phyllanthus emblica juice was established by using the multidimensional value theory of "reasonably-satisfaction". The comprehensive ranking was 'Bingtian'>'Chipi'>'Boli'>'Baiyu'>'Lingshan No.4'>'Pingdan No.1'>'Shuijing'>'Zhishengmiao', which had a high positive correlation with the ranking results of sensory evaluation. This study can provide theoretical reference for the selection of Phyllanthus emblica juice varieties in Guangdong and Guangxi areas.